2015
DOI: 10.1002/jemt.22544
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of epidermal growth factor system in the lung of the Japanese quail (Coturnix coturnix japonica) during the post-hatching period

Abstract: The purpose of this study is to determine the possible changes in the localization of the four Epidermal Growth Factor Receptors and three ligands in quail lungs from the first day of hatching until the 125th after hatching using immunohistochemical methods. Immunohistochemical results demonstrated that four EGFRs and their ligands are chiefly located in the cytoplasm of cells. Additionally, ErbB4, AREG, and NRG1 are localized to the nucleus and nucleolus, but EGF is present in the nucleolus. ErbB2 was also fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
(166 reference statements)
1
0
0
Order By: Relevance
“…Therefore, our study which focused on various types of mucins, particularly MUC1 and MUC4, in the respiratory system of the Iraqi common quail is consistent with these previous reports. Studies conducted on Japanese Quail indicated the presence of variable mucin types, including both neutral and acidic mucins, which exhibited changes corresponding to the post-hatching period of the Quail [44]. These findings are consistent with our results, which confirm the presence of a mixture of mucins, with acidic mucins being predominant over neutral mucins, and this predominance diminishes towards the lungs.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our study which focused on various types of mucins, particularly MUC1 and MUC4, in the respiratory system of the Iraqi common quail is consistent with these previous reports. Studies conducted on Japanese Quail indicated the presence of variable mucin types, including both neutral and acidic mucins, which exhibited changes corresponding to the post-hatching period of the Quail [44]. These findings are consistent with our results, which confirm the presence of a mixture of mucins, with acidic mucins being predominant over neutral mucins, and this predominance diminishes towards the lungs.…”
Section: Discussionsupporting
confidence: 91%